Advances in Slurry Technology (IntechOpen, 2023)
Written by experts from around the world, this book presents a comprehensive overview of slurry technology. The editor is grounded in the science of dilute concentrations of coarse particles in horizontal ducts, including settling distributions, critical deposition, swirling flow, and the two-layer model. This volume includes ten chapters that address such topics as process modelling, measurement (including non-Newtonian rheology), high-concentration conveying, vertical transport of fine-particle slurries, rheometry of sludges, pipe wear, and wastewater applications. There is also a chapter on an application at the fringe of our subject: fluidisation.